Judgement of the multidisciplinary team is an important predictor of mortality after cardiac resynchronization therapy - Luiz Carlos Santana Passos; Tainá Teixeira Viana; William Carvalho; Aline Grimaldi; Pollianna Roriz; Clara Figueiredo; Thais Nascimento; Rodrigo Morel Vieira de Melo (ESC Heart Failure, 2021)
Abstract Aims Cardiac resynchronization therapy (CRT) in appropriately selected patients with heart failure improves symptoms and survival. It is necessary to correctly identify patients who will benefit most from this therapy. We aimed to assess the predictive power of the multidisciplinary team's clinical judgement in the short‐term death after CRT implantation. Methods and results Patients with heart failure and referred for the first CRT implant were prospectively included. Prior to implantation, all patients underwent a systematic assessment with a team composed of social work, nurse, psychologist, nutritionist, and clinical cardiologist. Based on this assessment, patients could be contraindicated to CRT or referred to the procedure as favourable or unfavourable. All patients should complete 12 months of follow‐up; 172 patients were referred for CRT, 21 (12.2%) were contraindicated after the multidisciplinary team evaluation, 71 (47%) referred to CRT as non‐favourable implants, and 80 (53%) as favourable implants. All‐cause mortality occurred in only 2 (2.5%) patients in the favourable group and in 30 (42.3%) in the non‐favourable group, P < 0.001 (log rank). Among the 20 variables used as possible predictors of worse prognosis by the multidisciplinary team, four were independently associated with mortality in the follow‐up after the multivariate analysis: 1 year MAGGIC score between 40% and 49%, relative risk (RR) 5.0, 95% confidence interval (CI) 1.3–18.6, P = 0.016; poor pharmacological adherence, RR 4.9, 95% CI 1.6–15.6, P = 0.007; glomerular filtration rate <35 mL/min/1.73 m2, RR 3.0, 95% CI 1.1–8.5, P = 0.041; and right ventricular dysfunction, RR 2.6, 95% CI 1.2–5.7, P = 0.018. Conclusions The clinical judgement before the CRT implantation performed by a multidisciplinary team through the analysis of clinical and psychosocial variables is a strong predictor of short‐term mortality.